Deactivating deformation twinning in medium-entropy CrCoNi with small additions of aluminum and titanium. (15th March 2020) - Slone, C.E.; LaRosa, C.R.; Zenk, C.H.; George, E.P.; Ghazisaeidi, M.; Mills, M.J.
Abstract: High strain-hardening rates in equiatomic CrCoNi and other multi-principal element alloys have been attributed to deformation twinning. This work shows that small additions of Al and Ti to a CrCoNi alloy deactivate deformation twinning with only minor changes to uniform elongation and ultimate tensile strength. The initial microstructure is free of chemically ordered (Al, Ti)-rich precipitates after solutionizing and quenching. Tensile properties for the alloy are reported and compared to equiatomic CrCoNi, and the post-deformation microstructure is assessed. Density functional theory calculations indicate that energetically unfavorable Al-Al bonds may discourage shearing via partial dislocations, which are necessary for twinning to occur. Graphic abstract: Image, graphical abstract